The Potential of Iodine as A Treatment for Breast Cancer: A Narrative Review - Ibrahim, Raihan Syah; Elliyanti, Aisyah (Jurnal Kesehatan Manarang, 2023)
Breast cancer is a cancer with the highest incidence of death in women in the world. Studies state that breast cancer can capture iodine molecules, making this substance a potential alternative therapy for further research and study. Opportunities for iodine as a treatment for breast cancer are supported by the fact that iodine is a molecular element widely available in nature, such as in food, plants, and oceans, so iodine is an easy substance to obtain. This article explores the potential of iodine as a treatment for breast cancer. The method used is a literature review study, in which literature is collected through the PubMed, Science Direct, and Google Scholar databases published from 2013-2022, and full text is available. The results of the review of the 10 articles obtained are the exposure of sources and intake of iodine, the physiological effects of iodine, and the effects of iodine on breast cancer cells. Iodine has the potential as a substance with anticancer activity through antiproliferative mechanisms, apoptosis, and immune system activation when given in sufficient quantities and at appropriate doses. The mechanism of iodine affecting breast cancer cells occurs through direct and indirect effects on the biological processes of cancer cells. These mechanisms occur molecularly in cancer cells by intermediary mitochondrial organelles and specific ligands in the cell. Iodine can also be combined with breast cancer chemotherapy, such as doxorubicin, which gives a good treatment response after chemotherapy. This is important to ensure sufficient daily intake of iodine for the body, especially in patients with breast cancer.